2021
DOI: 10.15547/bjvm.2338
|View full text |Cite
|
Sign up to set email alerts
|

Tryptase- and ghrelin positive mast cells in the interalveolar septa of rat’s lung

Abstract: The mast cell mediators and distribution of lung mast cells in rats are often discussed in experimental studies on pulmonary fibrotic and allergic processes associated with changes in numbers of these cells, but information on the normal distribution of metachromatic and tryptase-positive mast cells in the interalveolar septa is scarce. There are no data on the presence of ghrelin in lung mast cells as well as the age-specific features of localisation and the number of mast cells in the interalveolar septa in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Therefore, the L. minor addition has a beneficial effect on BLM-induced inflammation and fibrotic processes, possibly participating in the Th1/Th2 immune response modulation and the subsequent decrease in the MCs and eosinophils set. Our results are supported by reports from a number of authors on the crucial role of mast cells and the Th2 immune response in IPF progression [16][17][18][21][22][23]69]. The accumulation of collagen together with increased MCs number in the interalveolar septa in BLM treated group detected in the current study correlates with the findings of several authors suggested that the MCs mediators tryptase, chymase and histamine induce lung fibroblast proliferation and collagen production [23,[70][71][72][73] recently demonstrated that stretch-induced degranulating MCs activate the pro-fibrotic cytokine TGF-β1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, the L. minor addition has a beneficial effect on BLM-induced inflammation and fibrotic processes, possibly participating in the Th1/Th2 immune response modulation and the subsequent decrease in the MCs and eosinophils set. Our results are supported by reports from a number of authors on the crucial role of mast cells and the Th2 immune response in IPF progression [16][17][18][21][22][23]69]. The accumulation of collagen together with increased MCs number in the interalveolar septa in BLM treated group detected in the current study correlates with the findings of several authors suggested that the MCs mediators tryptase, chymase and histamine induce lung fibroblast proliferation and collagen production [23,[70][71][72][73] recently demonstrated that stretch-induced degranulating MCs activate the pro-fibrotic cytokine TGF-β1.…”
Section: Discussionsupporting
confidence: 91%
“…Mast cells (MCs) derived from hematopoietic progenitors mature locally in lung tissue, and along with dendritic cells and macrophages, are among the first immune cells to be exposed to pro-inflammatory and toxic agents [15]. It is well-known that lung MCs synthesize mediators involved in the contraction of airway and lung smooth muscle cells, such as serotonin and ghrelin [16]. Inhibitory non-adrenergic non-cholinergic airway smooth muscle response is mediated by nitric oxide (NO) [17], and mast cells are a secondary source of NO-dependent relaxation of smooth muscle cells [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Volante et al (2002) observed by immunochemistry using a specific antibody that ghrelin-producing cells have a polygonal or elongated shape and are found in small clusters in fetal, infant, and adult human lungs. It has also been shown that ghrelin-positive cells in the lung are found mainly around the bronchi, in the bronchiolar wall, and in the alveolar septa (Ivanova et al 2021). Stefanov et al (2017 reported that in double immunofluorescence staining, both ghrelin and tryptase are expressed by the same MCs in rat stomachs.…”
Section: Ghrelin-immunopositive Cellsmentioning
confidence: 99%
“…Additionally, it was demonstrated that ghrelin-positive cells have a similar morphology and location to MCTs. Moreover, co-localization with tryptase immunoreactivity in serial sections from the porcine bile duct suggested that most ghrelin-positive cells might also be MCTs (Stefanov, 2021). Stefanov et al (2021) used immunohistochemistry to investigate the distribution of ghrelin cells and MCTs in the domestic pig and found that the numbers of ghrelin and tryptase immunoreactive positive cells both varied in parallel to the tunicas of the common hepatic duct.…”
Section: Ghrelin-immunopositive Cellsmentioning
confidence: 99%
See 1 more Smart Citation